Perbandingan Postur Kerja Dengan Metode Reba dan Qec Pada Pekerja Alat Kesehatan di PT. XYZ - Hanifah Dwi Lestari; Ratna Ayu Ratriwardhani; Moch. Sahri; Bondan Winarno (Jurnal Ilmiah Wahana Pendidikan, 2022)
Ergonomics hazard is one of the hazards caused by the relationship between work activities, use of tools, and a bad work environment that causes injury or illness to workers. In carrying out the work, it is still done manually and is done repeatedly in non-ergonomic and awkward positions every day for a long period of time. Therefore, there is a need for ergonomic hazards. This research was conducted in May 2022 using descriptive quantitative research. Ergonomics hazard risk level assessment using REBA (Rapid Entire Body Assessment) and QEC (Quick Exposure Checklsit) methods. The population in the study found 27 workers. The sample taken is 27 workers with total sampling technique. Data collection techniques were carried out using REBA worksheets and QEC questionnaires. The results showed that the ergonomic risk description using the REBA method was dominated by a moderate risk level of 20 workers, while the ergonomic risk description using the QEC method was dominated by a moderate risk of 21 workers. evaluation of the comparison of action levels using the REBA and QEC methods has resulted in 26 workers getting the risk level score at the same level. Each method that threatens ergonomics hazards has different characteristics and assessments in each body part so that it can affect the final score. Suggestions that can be recommended are to provide training on ergonomics to workers and provide facilities that make work easier